Effects of sparring load on reaction speed and punch force during the precompetition and competition periods in boxing - Hukkanen, E.; Häkkinen, K. (The Journal of Strength and Conditioning Research, 2017)
Seven, male, national-level boxers (age, 20.3 ± 2.7 years; height, 1.80 ± 0.06 m; mass, 73.8 ± 11.1 kg) participated in this study to investigate the effects of sparring on reaction time and punch force of straight punches measured during the precompetition and competition periods. Heart rate and blood lactate concentrations were also monitored. Sparring load was chosen in accordance with the current rules: 3 × 3-minute bouts with 1-minute break in between. Reaction time of rear straight lengthened (p < 0.01) during the sparring load of the precompetition period after the third round (to 390 milliseconds) in comparison to the competition period (to 310 milliseconds). Reaction time of lead straight lengthened (p = 0.05) between the first and third round during the precompetition with no differences during the competition period. Both rear and lead straight punch forces were greater at all measurement points during the precompetition compared with the competition period. Punch forces increased for both rear and lead straight between the first and third rounds with the highest forces after third round during the precompetition (rear straight, 209 kg) and competition (rear straight, 176 kg) periods. Blood lactate levels increased after every round during both periods being at its greatest after the third round (17 mmol·L-1 during the precompetition and 13 mmol·L-1 during the competition period). The present sparring-induced differences in reaction time and punch forces of straight punches during the precompetition compared with the competition period may be the result of different volume and intensity of training with different goals in boxing-specific and explosive strength training.